Extraction and evaluation of pectin methylesterase from Morinda citrifolia - Manee Saelee (2018)
© 2017 Manee Saelee et al. Morinda citrifolia Linn. (Noni) is used in traditional medicine. Pectinmethylesterases (PME) is an enzyme that is responsible for the degradation of pectin. The current study was aimed to extract PME from M. citrifolia (MPME) and compared with commercial PME, and studied the temperature mediated inactivation of PME. The results revealed that the optimum time, pH, and temperature of MPME was found as 5 min, pH 7, and 30°C, respectively. The pretreatment of M. citrifolia for 5 min at 100°C can significantly prevent the methanol formation. Further detailed study on the purification and characterization of MPME and the influence of pretreatment of M. citrifolia on methanol formation under progress.